Gut mucosal mycobiome profiling in Crohn’s disease uncovers an AMP-mediated anti-inflammatory effect of Cladosporium sphaerospermum - Huang, Ziyu; Liu, Yunyun; Wu, Yushan; Zhang, Feng; Yu, Leyi; Gao, Shanshan; Wen, Weijie; Wang, Guannan; Su, Runping; Xia, Pei; Zhou, Qiming; Bie, Yiran; et al. (Nature metabolism, 2026)
Crohn’s disease (CD) is a subtype of inflammatory bowel disease that most commonly affects the terminal ileum and is associated with abnormal gut microbiome composition. However, the fungi of the small bowel mucosa and their metabolic functions, particularly protective ones, remain largely unexplored. We enrolled patients with CD and healthy individuals from three independent cohorts and conducted multi-omics profiling of the ileal mucosal mycobiome and bacteriome, along with the faecal mycobiome, bacteriome and metabolome. We show that compared to a healthy mucosa, the fungus Cladosporium sphaerospermum is remarkably depleted in the mucosa of patients with CD, yet remains unchanged in faeces. Subsequent causality studies reveal that C. sphaerospermum occupies the intestinal crypt niche and counteracts intestinal inflammation partly by adenosine 5′-monophosphate (AMP) production, as demonstrated in mice, in vitro and in fungal cultures. Mechanistically, C. sphaerospermum upregulates epithelial cell junctions and the Wnt signalling pathway. Our study unveils a mucosa-associated beneficial fungus, suggesting potential novel microbial intervention strategies for CD.
Gesehen am 10.02.2026